Disclosure of Medical Secrets in Handling Corona Virus Disease (COVID)-19 Cases (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Novel Coronavirus or better known as Corona Virus Disease (COVID) 19 is a disease that first appeared in China in early December 2019. The disease quickly spread throughout China to Europe, the United States, Southeast Asia and Africa. Covid-19 is spread through droplets (particles) that come out through the human mouth when talking to others. This virus can infect everyone if the person is in contact with a covid-19 positive sufferer. So much for the ability of this virus to infect and spread is proven by the record that so far there are still many people infected with Covid-19 with increasing numbers.Method: This research method is a juridical-normative legal analysis. Legal research is based on the legal concept used.Results: The key to limiting the Covid-19 virus is that after knowing that something has been confirmed positive, tracing is immediately done to anyone who comes into contact with the patient. After all tracing is found, then a new examination is carried out whether they are also infected or not. Conclusion: There are several laws and regulations governing the opening of Patient Medical Rahasi, namely Law No. 36 of 2009 on Health and Regulation of the Minister of Health No. 269 of 2008 on Medical Records, which explicitly explains that related to the Covid-19 Pandemic is allowed to be opened Medical Secrets of patients concerning the interests and safety of thepublic.
Keywords: Covid-19 Cases, MedicalSecrets, Patient, Doctor, Disclosure